The miracle the epic story of Asia's quest for wealth - Schuman, Michael 1968- (Harper Business, an imprint of HarperCollins Publishers, 2009)
"In little more than a generation, Asia has emerged from centuries of stagnation to become the rising force of the global economy. This transformation has been so spectacular that some have called it a miracle. How did it happen? Taking the reader from the dockside's of Korea to the halls of India's finance ministry, The Miracle details the courageous decisions and heroic self-sacrifice that made Asia's ascent possible. Spanning nine countries and probing major historical currents, this account illuminates not only Asia's extraordinary economic rise but also how its causes might emancipate the developing world from poverty and guide the developed world to further prosperity. Using more than a decade of reporting and analysis, Time magazine and former Wall Street Journal reporter Michael Schuman uncovers how outsourcing to Asia began; how Asia's most famous companies, such as Sony and Honda, became global corporations; and how technological changes and global economic shifts made Asia's boom possible. He reveals the compelling human side to this economic story, introducing readers to the political strongmen, entrepreneurs, and policymakers who made the Miracle a reality. This engaging historical narrative brings to life the ideas and actions of a diverse group of Asians-dictators and democrats, generals and technocrats, economists and engineers. Some of the characters in the book have captured the global imagination for years, such as China's reformer Deng Xiaoping and Sony founder Akio Morita. Others are less well known, including Park Chung Hee, Korea's tightfisted nation builder; Liu Chuanzhi, the risk-taking founder of PC maker Lenovo; and Azim Premji, the mastermind behind Wipro, one of India's technology giants. All of them shared a dream-to elevate Asia to its proper place of influence in the world and eradicate the poverty around them. The Miracle not only offers profound insight into Asia and its increasing wealth and power; it also reveals how these seismic shifts continue to reverberate through the global economy. The implications of Asia's economic ascent for the rest of the world are surprising, promising, and inspiring. Readers of The Miracle will gain a deep understanding of Asia's place in the global economy--and of their own."